Joint Venture under the 1960 Commercial Code of Ethiopia: A Comparative Analysis with the UK and German Legal Systems - Demeke, Seid (Bahir Dar University Journal of Law, 2022)
The Ethiopian joint venture law is comparable with German and Englishlaws in respect of confidentiality. In relation to nature, transfer ofshares, liability of partners, and profits and losses distribution policy, theEthiopian joint venture law is more related with the English one. Whereas,with regard to the requirement of written agreement, the Ethiopian law ismore parallel with that of the German silent partnership since in bothcountries such requirement is waived by their respective laws. Additionally,concerning the â€œwho managesâ€ issue, it can be said that at least in terms ofcomposition and structure, the Ethiopian law is more comparable with theGerman silent partnership. This Article comes up with some best experiencesto Ethiopia drawn from the comparative analysis. It urges some prudentlegal framework to be espoused for the proper practice of joint ventures, i.e.in the way it addresses the ever more pressing needs for joint ventureengagements in Ethiopia. Accordingly, some legal improvements will besuggested, mainly, on issues of confidentiality, dissolution, and the need forwritten agreement.